Analysis of Evidence for the Crime of Money Laundering That Does Not Require Preliminary Proof of the Predicate Crime - Musdayanti; Abd. Asis; Audyna Mayasari Muin (LEGAL BRIEF, 2022)
This study aims to analyze the the Legislative Ratio Article 69 UURI No. 8 of 2010 concerning Prevention and Eradication of the Crime of Money Laundering that Does Not Require Proof of Excess Preliminary Crime in the Crime of Money Laundering. The research was conducted using a normative juridical research method using a statutory approach, a case approach, and a conceptual approach. The results of the study indicate that the process of handling money laundering cases is essentially very dependent on the original crime as contained in the provisions of Article 2 UURI No. 8 of 2010 which is an element in the crime of money laundering must come from a criminal act. In line with the above basis, Article 69 has been formulated which reads “In order to be able to carry out investigations, prosecutions, examinations in court proceedings against the crime of money laundering, it is not necessary to first prove the original crime”. Where the crime of money laundering can be investigated, prosecuted, and brought to court without having to first prove the original crime and not having to wait for the verdict of the predicate crime which has permanent legal force (inkracht).